Pengaruh Independensi, Skeptisisme, Dan Gender Terhadap Pemberian Opini Audit Melalui Pertimbangan Materialitas - Nevyra, Hendang Tanusdjaja (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of this study is to examine the analysis of independence, skepticism, and gender in the precision of the provision of the auditor’s opinion and with consideration of levels at the public accounting firm in the city of Jakarta. The sampling method used is a saturated sample of 94 respondents. Analysis of hypothesis testing data using SmartPLS (Partial Least Squares) version 3.3.2 and Microsoft Excel 2010. The results of this study indicate that auditor’s independence has a positive influence on materiality considerations and skepticism has a positive influence on materiality considerations, meanwhile, gender has a negative influence on materiality considerations. On the other side, independence, skepticism, and gender have a negative effect on the accuracy of the auditor's opinion giving consideration materiality levels, and consideration of materiality as mediating variables cannot affect auditor's opinion.